A Systematic Review of the Potential Chemoprotective Effects of Resveratrol on Doxorubicin-Induced Cardiotoxicity: Focus on the Antioxidant, Antiapoptotic, and Anti-Inflammatory Activities. (23rd August 2021) - Hu, Li-Feng; Lan, Huan-Rong; Li, Xue-Min; Jin, Ke-Tao
Abstract : Purpose . Although doxorubicin chemotherapeutic drug is commonly used to treat various solid and hematological tumors, its clinical use is restricted because of its adverse effects on the normal cells/tissues, especially cardiotoxicity. The use of resveratrol may mitigate the doxorubicin-induced cardiotoxic effects. For this aim, we systematically reviewed the potential chemoprotective effects of resveratrol against the doxorubicin-induced cardiotoxicity. Methods . In the current study, a systematic search was performed based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline for the identification of all relevant studies on "the role of resveratrol on doxorubicin-induced cardiotoxicity" in the electronic databases of Web of Science, PubMed, and Scopus up to March 2021 using search terms in their titles and abstracts. Two hundred and eighteen articles were screened in accordance with a predefined set of inclusion and exclusion criteria. Finally, 33 eligible articles were included in this systematic review. Results . The in vitro and in vivo findings demonstrated a decreased cell survival, increased mortality, decreased heart weight, and increased ascites in the doxorubicin-treated groups compared to the control groups. The combined treatment of resveratrol and doxorubicin showed an opposite pattern than the doxorubicin-treated groups alone. Furthermore, this chemotherapeutic agent induced the biochemical and histopathological changes on the cardiac cells/tissue; however, the results (for most of the cases) revealed that these alterations induced by doxorubicin were reversed near to normal levels (control groups) by resveratrol coadministration. Conclusion . The results of this systematic review stated that coadministration of resveratrol alleviates the doxorubicin-induced cardiotoxicity. Resveratrol exerts these chemoprotective effects through several main mechanisms of antioxidant, antiapoptosis, and anti-inflammatory.